2011
DOI: 10.1111/j.1468-0459.2011.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Preface: the international polar year project ‘kinnvika’– arctic warming and impact research at 80° n

Abstract: Pohjola, V.A., Kankaanpää, P., Moore, J.C. and Pastusiak, T., 2011. The International Polar Year Project ‘KINNVIKA’– Arctic warming and impact research at 80° N. Geografiska Annaler, Series A, Physical Geography, 93, 201–208. DOI: 10.1111/j.1468‐0459.2011.00436.x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…1A), and lies between the Vestfonna glacier (∼8 km) and Isvika bay (∼0.5 km) in the southern Murchisonfjorden (Fig. Mean annual and July air temperatures in the region are −8 and +2°C, respectively (Pohjola et al 2011). Lake Einstaken drains into Isvika bay and is occasionally connected to adjacent Lake Krystallvattnet (64 m a.s.l.)…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…1A), and lies between the Vestfonna glacier (∼8 km) and Isvika bay (∼0.5 km) in the southern Murchisonfjorden (Fig. Mean annual and July air temperatures in the region are −8 and +2°C, respectively (Pohjola et al 2011). Lake Einstaken drains into Isvika bay and is occasionally connected to adjacent Lake Krystallvattnet (64 m a.s.l.)…”
Section: Study Sitementioning
confidence: 99%
“…The bedrock consists of dolomites, limestones, shales and sandstones, and the catchment is characterized by highly weathered substrates, discontinuous till patches, and periglacial features with extremely scarce vegetation (scattered Saxifraga, Dryas and mosses) and undeveloped soils. Mean annual and July air temperatures in the region are −8 and +2°C, respectively (Pohjola et al 2011).…”
Section: Study Sitementioning
confidence: 99%
“…The catchment is comprised of arctic desert with an annual precipitation about 400 mm of (Hagen et al 1993), most of it as snow. The mean annual temperature is −8°C, and that of July about +3°C (Pohjola et al 2011).…”
Section: Regional Settingmentioning
confidence: 99%
“…Annual and seasonal temperatures have been generally rising, and the sea−ice extent and volume have been declining with an ice loss unmatched in the last thousand years and unexplainable by any known natural variabiliy (e.g. Solomon et al 2007;Kwok et al 2009;Polyak et al As one of the activities of the International Polar Year 2007Year -2009, an expedition was organised to the Murchisonfjorden area, Nordaustlandet (Pohjola et al 2011). Earlier studies by Kaakinen et al (2009) and Kubischta et al (2010) indicated that coastal sections in Isvika bay contain glacial and marine sediment sequences extend− ing back to the beginning of the Weichselian glacial stage.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of the IPY (International Polar Year) Kinnvika project (Pohjola et al . 2011) and its follow‐on activities several field campaigns with focus on snow‐cover related fieldwork were carried out during seven individual field campaigns on Nordaustlandet, Svalbard, in the period 2007–2010.…”
Section: Introductionmentioning
confidence: 99%